Akibat Hukum Harta Hibah Terhadap Pembatalan Akta Hibah yang Dibuat PPAT - Ramadhanti, Annisa Rizqy; Santoso, Budi (Syntax Corporation, 2025)
This writing aims to determine the principle of the cancellation of the grant deed based on Article 1688 of the Civil Code and the legal consequences of the grant property for which the cancellation of the grant is requested. The principle of canceling the grant deed is based on Article 1688 of the Civil Code, that is, if the grantee's requirements are not met by the grantee, the grantor can request the return of the gifted goods. If the recipient of the grant is proven to be involved in a crime or murder against the grantor himself. If the grantor falls into poverty and the recipient is reluctant to provide a living to the grantor, the grant can be returned to the grantor. The occurrence of a grant cancellation can cause legal consequences for the grant goods through a decision to cancel the grant from the Court by making the ownership rights to the grant property return to the grantor. Thus, all of the grant assets become the property of the grantor. If the grant item has been certified on behalf of the grant recipient, the certificate is not valid.